The efficacy and safety of 125I brachytherapy combined with pre-operative transarterial chemoembolization in patients with locally advanced head and neck cancer - Zhang, Menglong; Zhang, Jian; Hu, Bijuan; Huang, Liyin; Song, Shanjun; Zhu, Haitao; Chen, Chao; Chu, Cunkun (Frontiers in Oncology, 2022)
Objective: To evaluate the safety and effectiveness of Iodine-125 (125I) brachytherapy combined with pre-operative transarterial chemoembolization in patients with locally advanced head and neck cancer. Methods: Thirty-seven patients with locally advanced head and neck cancer enrolled in this study. All of them underwent transarterial chemoembolization and followed by implantation of 125I seeds under the guidance of CT and ultrasonography. Follow-up was conducted for 36 months to observe the local control rate, survival rate, and clinical complications. Results: The objective response rate and disease control rate of the 37 cases at 3 months were 69.8% and 93.0%, respectively. The 1, 2, 3-year cumulative overall survival rate was 89.2％, 73.0％,45.9％, respectively. Adverse events included infection (n=1, Grade III), radiation brachial plexus injury (n=1, Grade III), leukopenia (n=1, Grade III), cerebrovascular embolism (n=1, Grade IV). Conclusion: The combination of 125I brachytherapy and pre-operative transarterial chemoembolization was safe and effective in patients with locally advanced head and neck cancer. [Key words] Brachytherapy, Chemoembolization, Head and Neck Cancer, Intervention, Efficacy